Exploring the features of stratification phenomena for 3D flow of Cross nanofluid considering activation energy. (July 2020) - Ali, Mehboob; Shahzad, Muhammad; Sultan, Faisal; Khan, Waqar Azeem; Rashid, Sheikh
Abstract: To explore the features of three-dimensional incompressible flow of Cross fluid with combine convective and stratifcation phenomena. Futhermore, Brownian and thermophoresis effect of nanoparticles is considered for investigation of magnetic field, thermal radiation, heat sink/source and activation energy. The governing set of non-linear partial differential equations (PDE's) is converted to the set of ordinary differential equations (ODE's) with the assistance of self-similar transformations. These non-linear equations are solved numerically by using boundary value problem default solver in MATLAB bvp4c package. The influence of different fluid flow parameters on the velocity, temperature, and concentration profiles are analyzed graphically. Also, the local skin friction coefficients, the rate of heat and mass transfers are presented and discussed through tables. Moreover, the present investigation reports that the mixed convection decline the liquid temperature for both shear thickening/thinning liquids.